UNDERSTANDING OF SPEECH ACTS USED IN â€œTHE RON CLARK STORYâ€ MOVIE - Sarair Sarair (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2018)
This research aimed to analyze the studentsâ€™ understanding of speech acts used in The Ron Clark Story movie. In this movie the writer found that there are many types of speech acts used that consisted of direct, indirect speech acts, literal and non literal speech act. The total of each types of speech acts found in the movie are 287 direct speech acts, 72 indirect speech acts, 343 literal speech acts and 16 non literal speech acts. The data were analyzed based on Searle theory of types of speech acts that consisted of representative, directive, commissive, expressive, and declarative. This study used quantitative research method. The sample of this research is the students of 7th semester of Muhammadiyah Aceh University. Total sample of this research is 14 students. The instrument used is paper test that contained 50 questions. The questions consisted of 8 representatives, 12 directives, 10 commissives, 11 expressives, and 9 declaratives. The result of this research showed that the level of studentsâ€™ understanding was poor. The students made 65% error in classifying representative, 75% error in classifying directive, 61% error in commissive, 37% error in expressive and 85% errors in declarative.Keywords: speech acts, representative, directive, commissive, expressive and declarative.